2020
DOI: 10.46328/ijres.v6i4.1136
|View full text |Cite
|
Sign up to set email alerts
|

Middle School Students’ Graph Skills and Affective States about Graphs

Abstract: This survey design study was designed to test whether the graph skills and affective states of middle school students about graphs differ by their gender, grade level, and graph types (line, bar, and pie). The data collection instruments consisted of two scales developed by the authors and a Graph Skills Test, which consisted of graph questions from the previous TIMSS and PISA exams. Based on the findings, while middle school students were found to succeed at reading the data level graph questions, they were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 35 publications
1
12
0
3
Order By: Relevance
“…Regarding the affective states examined, it was discovered that individuals had high selfefficacy beliefs and favourable opinions toward graphs. Gender did not significantly affect the dependent variables (graph skills, self-efficacy beliefs about graphs, attitudes toward graphs, and personal perceptions of graph literacy); however, grade level and graph type variables did affect students' graph skills, attitudes toward graphs, and personal perceptions of their own graph literacy (Bursal Yetis, 2020).…”
mentioning
confidence: 63%
“…Regarding the affective states examined, it was discovered that individuals had high selfefficacy beliefs and favourable opinions toward graphs. Gender did not significantly affect the dependent variables (graph skills, self-efficacy beliefs about graphs, attitudes toward graphs, and personal perceptions of graph literacy); however, grade level and graph type variables did affect students' graph skills, attitudes toward graphs, and personal perceptions of their own graph literacy (Bursal Yetis, 2020).…”
mentioning
confidence: 63%
“…Bursal (2019) ortaokul Fen dersi için grafik türlerine göre grafik okuryazarlığı ölçeği geliştirmiştir. Bu çalışmalarda elde edilen sonuçlardan hareketle farklı derslere ilişkin araştırılmalar yapılsa da ulaşılan sonuçlar açısından benzer biçimde öğrencilerin grafikte yer alan verileri okumada iyi sayılabilecekleri ancak grafikleri düşük düzeyde yorumlayabildikleri görülmektedir (Bursal ve Yetiş, 2020;Güler ve Didiş Kabar, 2021). Benzer şekilde de Özmen vd.…”
Section: çAlışmanın öNemiunclassified
“…Considering the role of teachers in helping students become graphically literate, it is important that teachers also have these skills. When the literature is examined, it is seen that the studies on graphs are generally carried out with students (Arteaga et al, 2021;Bolch & Jacobbe, 2019;Bragdon et al, 2019;Bursal & Polat, 2020;Bursal & Yetis, 2020;Díaz-Levicoy et al, 2019;Galesic & Garcia-Retamero, 2010;Glazer, 2011;Guler, 2019;Hotmanoglu, 2014;Kaynar & Halat, 2012;Ozmen et al, 2020;Selamet, 2014;Sezgin-Memnun, 2013;Wu, 2004). Bolch and Jacobbe (2019) examined the graph comprehension of university students within the scope of the evaluation questions in the levels of conceptual understanding in statistics (LOCUS) project, which was carried out to improve students' statistical understanding.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is stated that the students mostly have difficulty with the questions that require reading the circle graph. Bursal and Yetis (2020), in their study to determine the graphs skills of seventh and eighth-grade students, revealed that students can reading the graphs, but their interpreting the graphs and drawing skills are insufficient. Wu (2004) evaluated the graph comprehension of 907 students with 13 and 15 years at four levels: reading the graph, interpretation the graph, drawing the graph and evaluating the graph.…”
Section: Introductionmentioning
confidence: 99%